2020
DOI: 10.1021/acs.cgd.0c01325
|View full text |Cite
|
Sign up to set email alerts
|

Linking Aggregation in Solution, Solvation, and Solubility of Simvastatin: An Experimental and MD Simulation Study

Abstract: The solubility is generally thought to be higher if the solvent effectively solvates solute molecules that are wellseparated from each other. The present work suggests, however, that the formation of large solute aggregates does not necessarily imply less effective solvation and lower solubility. Measurements of the solubility of simvastatin (one of the most commonly prescribed antihyperlipidemic drugs) in three solvents with different polarities and protic characters, led to the solubility order acetone > eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Previous experiments carried out with pure organic solvents suggest, however, that both these effects may be significant in an evaporative crystallization process. Their influence was, therefore, investigated in this work by adding thermographic analysis to the above mentioned techniques (X-ray diffraction, Raman spectroscopy, and imaging) and complementing the experimental information with MD simulation results. The crystallization of simvastatin (Figure ) in acetone, ethyl acetate, and ethanol was selected as a model system, due to the variety of crystalline and amorphous forms that may be obtained and the complex solubility behavior in these solvents already characterized in a previous work …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experiments carried out with pure organic solvents suggest, however, that both these effects may be significant in an evaporative crystallization process. Their influence was, therefore, investigated in this work by adding thermographic analysis to the above mentioned techniques (X-ray diffraction, Raman spectroscopy, and imaging) and complementing the experimental information with MD simulation results. The crystallization of simvastatin (Figure ) in acetone, ethyl acetate, and ethanol was selected as a model system, due to the variety of crystalline and amorphous forms that may be obtained and the complex solubility behavior in these solvents already characterized in a previous work …”
Section: Introductionmentioning
confidence: 99%
“…Simvastatin is a widely used API for treatment of hyperlipidemias and prevention of cardiovascular diseases that can exist in three polymorphic forms. Form I is the thermodynamically stable one under ambient conditions. The III/II and II/I pairs are both enantiotropically related by reversible solid–solid-phase transitions: form III → form II at 236.9 K and form II → form I at 275.2 K. , Furthermore, amorphous phases with very long lifetimes have been reported. Information about the complexity of simvastatin solvation and aggregation processes has also been recently provided by a study combining solubility measurements in acetone, ethyl acetate, and ethanol with molecular dynamics (MD) simulations . These solvents seemed therefore appropriate for the present study due to their significantly different volatility, hygroscopicity, polarity, and protic character.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to use MD simulation methods to quantitively compute the solubility of water. Still, several studies demonstrated that this methodology may be used to rationalize solubility trends from the analysis of the molecular aggregation patterns in solution. Thus, in this work, MD simulation data were explored as a qualitative approach for comparison with the QSPR results.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Although the computation of solubility values from molecular dynamics (MD) simulations is a nontrivial process, this theoretical approach has proved valuable in the rationalization of mixability trends. Unlike QSPR, this method provides a molecular view of the interaction between the molecules in solution, enabling a physical explanation of the experimentally observed liquid–liquid phase diagrams. One approach to investigate solubility trends involves the search for aggregation patterns of molecules in solution and how these networks (or their absence) may suggest that liquid–liquid phase separation is likely to occur. , For example, if we consider the formation of water aggregates in an IL, a high probability of finding aggregates composed of many molecules of water may suggest that, most likely, the interaction between water and the IL is inefficient and a liquid–liquid phase separation may be eminent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation